Local VEGF‐A blockade modulates the microenvironment of the corneal graft bed. Issue 9 (3rd April 2019) - Salabarria, Ann‐Charlott; Braun, Gabriele; Heykants, Malte; Koch, Manuel; Reuten, Raphael; Mahabir, Esther; Cursiefen, Claus; Bock, Felix
Abstract : The microenvironment plays an important role in several immunological processes. Vascular endothelial growth factor‐A (VEGF‐A) not only regulates angiogenesis, but is known as a modulator of the immune microenvironment. Modulating the site of transplantation might be beneficial for subsequent transplant survival. In this study, we therefore analyzed the effect that a local blockade of VEGF‐A in the inflamed cornea as the graft receiving tissue has on the immune system. We used the murine model of suture‐induced neovascularization and subsequent high‐risk corneal transplantation, which is an optimal model for local drug application. Mice were treated with VEGFR1/R2 trap prior to transplantation. We analyzed corneal gene expression, as well as protein levels in the cornea and serum on the day of transplantation, 2 and 8 weeks later. Local VEGF depletion prior to transplantation increases the expression of pro‐inflammatory as well as immune regulatory cytokines only in the corneal microenvironment, but not in the serum. Furthermore, local VEGFR1/R2 trap treatment significantly inhibits the infiltration of CD11c+ dendritic cells into the cornea. Subsequent increased corneal transplantation success was accompanied by a local upregulation of Foxp3 gene expression. This study demonstrates that locally restricted VEGF depletion increases transplantation success by modulating the receiving corneal microenvironment and inducing tolerogenic mechanisms. Abstract : In the murine high‐risk corneal transplantation model, local VEGF depletion by topical eye drops increases transplantation success by modulating the receiving corneal microenvironment.